Biosorption of fluoride from aqueous solutions by Rhizopus oryzae: Isotherm and kinetic evaluation. Issue 1 (30th July 2021) - Tangestani, Mahbubeh; Naeimi, Behrouz; Dobaradaran, Sina; Keshtkar, Mozhgan; Salehpour, Parisa; Fouladi, Zahra; Zareipour, Samaneh; Sadeghzadeh, Farzaneh
Abstract: Removal of high fluoride contents from aqueous solutions by inexpensive, and biocompatible biosorbent is a main concern for human health. In the present study the efficacy of Rhizopus oryzae fungal biomass in removal of fluoride from aqueous solutions considering the effects of different parameters such as contact time (10–180 min), initial fluoride concentration (2–10 mg/L), and biosorbent dose (0.25–2 g/L) was studied in a batch system. The optimum condition for the maximum fluoride biosorption (90.5%) was obtained at 2 g/L biosorbent dose, 30 min contact time and 2 mg/L initial fluoride concentration. The Langmuir model ( R 2  = 0.9844) fitted better than the other models and showed a homogeneous biosorption surface with the possibility of a monolayer biosorption of fluoride by biosorbent. The Langmuir maximum biosorption capacity of fluoride for R. oryzae was obtained at 1.16 mg/g. The biosorption kinetic was controlled by the pseudo‐second‐order ( R 2  = 0.9999) model and based on the intra‐particle diffusion model; the fluoride biosorption rate was not controlled only by the mechanisms of intra‐particle diffusion. Consequently, the results showed that fungal biomass can be used as a suitable biosorbent for fluoride removal from aqueous solutions.